The Role of Strategic Leadership in Achieving The Institutional Maturity in Arab Public Organizations »Proposed Vision« - Mohamed, Abdelrahim (The Arab Journal of Administration, 2019)
The strategic leadership is plying important role in the organization success and achieving its vision and mission, this happens throw the skills and capabilities that the strategic leadership have and helping him to make changes to empower the organization follow the environmental changes and has the ability to continue and thrive, this required from the organization a group of criteria to choose the strategic leaders. Illustrated from the literatures review that related to strategic leadership, there is no studies focused on the concept of institutional maturity in Arab Public organizations in addition to need this organizations for methodology involved criteria helping it in selecting the strategic leaders to achieve the institutional maturity. The problem of the research seeks to answer some questions, are the criteria of selecting strategic leaders that the public organizations that are using to know can empower it to select excellent leader? Are the current leaders in Public organizations plying role to achieve the institutional maturity? The research found there is a weak in the public organizations toward institutional maturity also weak in the role of strategic leadership in identify criteria to select strategic leaders and prepare the second role of leaders. The research recommended with proposed vison aim to discover the strategic leaders and prepared for the future also included numbers of criteria the organizations must fowled it when select the people to leadership positionsel of )0.174(.